Analisis ANALISIS TENTANG KEKUATAN PEMBUKTIAN KETERANGAN AHLI DALAM PROSES PEMERIKSAAN PERKARA PIDANA DI SIDANG PENGADILAN: ANALISIS TENTANG KEKUATAN PEMBUKTIAN KETERANGAN AHLI DALAM PROSES PEMERIKSAAN PERKARA PIDANA DI SIDANG PENGADILAN - Maria Ferba Editya Simanjuntak (JURNAL HUKUM DAS SOLLEN, 2022)
In Article 184 of the Criminal Procedure Code, various types of evidence are mentioned one of which is the inclusion of expert evidence. In addition to the role of experts related to the provision of information tha should be neutral, impartial, experts also encounter obstacles that occur during the inspection process, such as difficulties in giving information in front of a judge or public prosecutor due to different educational backgrounds. This study aims to determine the legal arrangements regarding evidence in criminal cases and to determine the legal position of expert testimony as evidence in criminal cases. The type of research in writing this thesis is carried out with normative legal research in the form of library research using 3 legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. This legal research focuses on literature study, which means it will study more and examine the existing and applicable legal rules. This research was conducted with the aim of know what the purpose of proof is through tools valid evidence according to KUHP and what is the position of expert testimony as evidence in the examination of a criminal case. The results show that the essence of the evidentiary process is to seek the material truth of an event that occurred in the past and to give confidence to the judge about the incident so that the judge can give the fairest decision. That way it can be seen that the testimony of an expert has an important role in the process of examining criminal cases in court.